2020
DOI: 10.3233/npm-190266
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal management and outcomes of pregnancies with congenital diaphragmatic hernia

Abstract: BACKGROUND: The objective of this study is to evaluate the obstetric outcomes of pregnancies with congenital diaphragmatic hernia (CDH). METHODS: Fifty one pregnancies prenatally diagnosed with CDH at our institution between January 1, 2002 and August 31, 2018 were retrospectively evaluated. The pregnancies were divided into two groups according to neonatal survival. Demographic features, clinical characteristics and prognostic factors were compared between the neonatal survival (n = 16) and non-survival (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Tanacan et al similarly classified the location of the stomach in their study of 44 pregnant women with CDH. They found that the stomach was in the abdomen in more than 50% of the surviving neonates, second most commonly in the anterior left thorax (19). Our study found a grade 2 stomach position in 50% of the surviving infants, suggesting an increased survival rate.…”
Section: Table 2 Comparison Of Stomach Position Degrees Among Neonata...supporting
confidence: 53%
“…Tanacan et al similarly classified the location of the stomach in their study of 44 pregnant women with CDH. They found that the stomach was in the abdomen in more than 50% of the surviving neonates, second most commonly in the anterior left thorax (19). Our study found a grade 2 stomach position in 50% of the surviving infants, suggesting an increased survival rate.…”
Section: Table 2 Comparison Of Stomach Position Degrees Among Neonata...supporting
confidence: 53%
“…[ 12 ] LHR <1 carries a poor survival, with a value <0.6 carrying 100% mortality. [ 13 ] In our series, of five foetuses with antenatal diagnosis of CDH, two cases with LHR of 0.6 and 0.9 died immediately after birth. Rest of the 3 (60%) with an average LHR >1 underwent surgery and are surviving in good health at 2-year follow-up.…”
Section: Discussionmentioning
confidence: 78%
“…Many studies have pointed out that o/e FLV is a prognostic factor for mortality [ 7 , 16 , 21 , 22 , 23 , 24 ]. Cordier et al reported a link between o/e FLV and mortality: an o/e FLV < 15% was associated with mortality in 88% of cases with upward liver migration.…”
Section: Discussionmentioning
confidence: 99%